METHODOLOGICAL APPROACHES TO DEVELOPING PREPARATION FOR INCLUSIVE EDUCATION IN THE PROFESSIONAL TRAINING SYSTEM (Web of Technology: Multidimensional Research Journal, 2024)
The article focuses on the pedagogical and psychological aspects of education for children with disabilities through inclusive education, provides information on the tasks carried out to the aamla on accelerating intellectual development, training of competitive personnel, effective organization of scientific and innovative activities, and the focus on educational processes and inclusive education today.